Law Enforcement For Foreign Shipping Performing Illegal Fishing - Ferry Akbar; Evita Isretno Israhadi; Boy Nurdin (Journal Research of Social Science, Economics, and Management, 2023)
Illegal fishing on foreign vessels has a very bad impact on all traditional fishermen. And this will make coastal fishermen feel the impact of illegal fishing by foreign vessels. Apart from that, this will also have an impact on consumers who like to consume fish because fishermen are not found to be able to feel the results produced by the country where fishermen were born and grew up. If viewed from a macro perspective, this will make the prices obtained from Indonesian marine products higher. It is clear that currently, the international community is starting to pay attention to Indonesia's fishery area. In law enforcement in the field of fisheries, a criminal justice system is established that includes a more structured process and problem-handling system. However, criminal acts of illegal fishing by foreign fishing vessels still occur, both by Indonesian citizens and by foreign nationals. This type of research is normative research. The approach used is a statutory approach (statute approach) and a conceptual approach (conceptual approach). The source of data used is secondary data. Data analysis was carried out in a qualitative descriptive manner. Concluding is carried out using the deductive method, namely concluding from general to specific, especially those related to the research topic, namely law enforcement against Illegal Fishing. This research resulted in findings Illegal fishing will have a very bad impact on all traditional fishermen. And this will make coastal fishermen feel the impact of illegal fishing by foreign vessels.